Of Cargoes, Colonies and Kings diplomatic and administrative service from Africa to the Pacific - Stuart, Andrew (Radcliffe Press, 2001)
This book provides insights into the work of an experienced colonial administrator and diplomat at the height of Britain's involvement abroad. Andrew Stuart's wide-ranging experience included decolonization in Uganda, preparations for negotiations with China over Hong Kong, and revolutions in the Seychelles, Bangladesh.